Mathematical modeling of the uptake of curing salts in pork meat - Graiver, Natalia Gisel (2009)
A mathematical model was developed in order to represent the uptake of curing salts (NaNO2, KNO3, and NaCl) in pork meat pieces with the purpose of determining immersion times and suitable salt concentrations in the brine of wet curing processes. The partial differential equations of mass transfer Ander unsteady-state conditions were solved numerically, in three-dimensional geometry (finite cylinders), considering the diffusive and also the convective contributions of the different solutes, due to water uptake by the tissue. The variation of the diffusion coefficients of the curing salts with NaCl concentration was also considered. The numerical model was validated using results obtained from experiments of salt diffusion in pork meat cylinders of different diameters immersed in curing brines. The model was applied to predict the time necessary for an industrial piece of meat to be immersed in brine without exceeding the maximum permitted nitrite value of 200 ppm and the recomendable sodium chloride concentration.